Indian and Bangladeshi Perspectives: Use of Metacognition and Framing in Postgraduate Study - Bell, Joyce (Multilingual Matters Ltd., 2007)
The importance of reading for academic study cannot be overemphasised. At the postgraduate level in particular, students are faced with complex text interpretation processes. International students, in addition, have to make a significant cultural/study shift; not only do they have to become accustomed to the reading of academic texts using discipline-specific discourse patterns but often have to adjust to different conventions used by authors from cultural backgrounds other than their own. Despite difficulties which international postgraduate students may experience, reading problems and the expected outcomes have been cited as one of the most neglected areas of research. In addition, little is known about international student reading practices and how they change during study at an Australian university. This paper, part of a longitudinal study, using metacognitive and framing theories, explores aspects of framing and metacognition used by Indian/Bangladeshi postgraduate students when reading their texts during their first semester at an Australian university.